Problems of Self-Care Activities Encountered in Rheumatoid Arthritis and Their Relationship with Disease Activity and Hand Deformity - Mine KÖYBAŞI,; Figen AYHAN,; Pınar BORMAN,; Rezan YORGANCIOĞLU, (Archives of Rheumatology, 2011)
Objectives: We aimed to investigate the impairments in the following basic self-care domains of the Health Assessment Questionnaire (HAQ): dressing and grooming, eating, and hygiene and to determine the relationships between these impairments and disease activity and deformity in this study. Patients and methods: A total of 152 patients (113 females, 39 males; mean age 52.3±14.1 years; range 24 to 80 years) with rheumatoid arthritis were included in this study. Disease activity was measured by the American College of Rheumotology (ACR) tender and swollen joint counts, the visual analog scalepain (VAS-pain), patient and physician global assessments, the Disease Activity Score of 28 joints (DAS28), the erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP). The functional state was evaluated using HAQ. Results: The mean score of DAS28 was 4.5±1.4. The mean ACR tender and swollen joint counts were 11.1±1.9 and 0.7±0.2, respectively. The mean patient and physician global assessment scores were 5.2±2.5 and 4.7±2.4, respectively. There were statistically significant relationships between the functional limitations in all self-care domains of the HAQ and DAS28, ACR tender joint count, VAS-pain, patient and physician global assessment, ESR, and joint deformity (p<0.01). Cutting meat and getting on and off the toilet were the most affected self-care activities. Conclusion: Many impairments can be detected in self-care activities of patients with rheumatoid arthritis. Rehabilitation strategies should be developed according to the indicated impairment. The self-care domains of HAQ were found to be associated with clinical disease activity in this patient group.